2021
DOI: 10.1007/s12010-021-03684-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rhizospheric Bacterium: Bacillus velezensis NKMV-3 as a Biocontrol Agent Against Alternaria Leaf Blight in Tomato

Abstract: A novel strain of Bacillus isolated from rhizosphere has shown to be excellent biocontrol agents against various plant pathogens. In this study, a rst report of a Bacillus strain NKMV-3 which effectively controlling Alternaria solani, which cause the Early Blight disease in tomato. Based on the cultural and molecular sequencing of 16S rRNA gene sequence, the identity of the strain was con rmed as Bacillus velezensis NKMV-3. The presence of the lipopeptide which are antibiotic synthesis genes namely Iturin C, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Treatment with the organic extract of B157 at 2,5 mg/mL completely inhibits conidial germination of A. linariarie AS248P (data not shown). Iturins and a mixture of iturins and fengycins produced by two strains of B. velezensis were recently associated with in vitro mycelial growth inhibition of A. solani and early blight severity reduction on detached leaflets of potato and tomato (Zhang et al 2021;Vignesh et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the organic extract of B157 at 2,5 mg/mL completely inhibits conidial germination of A. linariarie AS248P (data not shown). Iturins and a mixture of iturins and fengycins produced by two strains of B. velezensis were recently associated with in vitro mycelial growth inhibition of A. solani and early blight severity reduction on detached leaflets of potato and tomato (Zhang et al 2021;Vignesh et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Soil samples were collected from tomato fields at Yanqi Basin, Xinjiang in August–September at a temperature of 28–31 °C and obtained from the layer, approximately 3 cm apart on the topsoil [ 37 ]. Tomatoes for the experiment were harvested in the Changji Hui Autonomous Prefecture, where they were free of visible wounds and uniform in size and maturity.…”
Section: Methodsmentioning
confidence: 99%
“…When the fungal mycelium of the blank control covers the entire petri dish, the width of the inhibition zone (the average distance between colonies), is measured, and calculating the inhibition rate. the formula is as follows: inhibition rate(%)=(control colony diameter-treatment colony diameter)/control colony diameter×100% Detached-leaf and in Fungi Inhibition Assays Detached leaf bioassays were conducted with slight modi cations as described by Murthy Vignesh (Vignesh et al 2022). Carefully remove some leaves of the same size from the potted tomato plants (20day), disinfect the leaves with 1% sodium hypochlorite, rinse with sterile water three times, and place them on a Vertical superclean bench for a period to dry the surface.…”
Section: Plant Pathogens' Growth Inhibition Assaysmentioning
confidence: 99%
“…PGPR have attracted worldwide attention in recent years in the control of various plant pathogens and promoting plant growth due to their low cost, easy production, environmental friendliness, and no residue effects. (Vignesh et al 2022) Bacillus species is one of the main bacteria found in soil (Saxena et al 2020a). Compared to other types of PGPR, Bacillus species has the outstanding property of being able to tolerate heat, radiation and some chemicals due to its ability to form spores (Setlow 2010), and is convenient to make various bacterial fertilizers or biocontrol agent for easy transportation and storage, which makes Bacillus species one of the most commercially useful bacteria in the agricultural biotechnology industry (Saxena et al 2020b).…”
Section: Introductionmentioning
confidence: 99%